Prevalence of Horns in a Pen Does Not Affect Incidence of Carcass Bruising in Feedlot Cattle - M. E. Youngers; E. F. Schwandt; D. U. Thomson; J. C. Simroth; S. J. Bartle; M Siemens; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
Disbudding and dehorning are two common practices done to remove horns from cattle to prevent injury to handlers and other cattle and to reduce bruising of carcasses. Bruised carcasses result in substantial reduction in profit due to trim loss, increased sanitation risk, and loss in time on the rail during processing. Previous research has indicated that cattle with horns increased hide damage of cohorts and caused injury to handlers. Cattle with horns cause circular shaped bruises that lead to trim loss due to bruising. Cattle with tipped horns do not have a lower bruising rate than cattle with intact horns. The objective of this study was to evaluate the effect of horn prevalence within groups of slaughter animals and the incidence of bruising on the carcasses of those same cattle.
Keywords: bruising; cattle; horns